Measurement of ZZ production cross-sections in the four-lepton final state in pp collisions at √s = 13.6 TeV with the ATLAS experiment - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Czurylo, Marta; Rio, Fernando del; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Junkermann, Thomas; Klassen, Martin; Mkrtchyan, Tigran; Ott, Philipp; et al. (Physics letters, 2024)
This paper reports cross-section measurements of ZZ production in pp collisions at s=13.6TeV at the Large Hadron Collider. The data were collected by the ATLAS detector in 2022, and correspond to an integrated luminosity of 29 fb−1. Events in the ZZ→4ℓ (ℓ=e, μ) final states are selected and used to measure the inclusive and differential cross-sections in a fiducial region defined close to the analysis selections. The inclusive cross-section is further extrapolated to the total phase space with a requirement of 66 <mZ< 116 GeV for both Z bosons, yielding 16.8±1.1 pb. The results are well described by the Standard Model predictions.
The ATLAS Collaboration: G. Aad, L. M. Baltes, F. Bartels, Marta Czurylo, F. Del Rio, S. J. Dittmeier, M. Dunford, S. Franchino, T. Junkermann, M. Klassen, T. Mkrtchyan, P. S. Ott, D. F. Rassloff, S. Rodriguez Bosca, C. Sauer, A. Schoening, H-C. Schultz-Coulon, V. Sothilingam, R. Stamen, P. Starovoitov, L. Vigani, S. M. Weber, M. Wessels, J. Zinsser [und viele weitere]
Gesehen am 07.10.2025